Cellular oxygen sensing: Crystal structure of hypoxia-inducible factor prolyl hydroxylase (PHD2). - McDonough, M; Li, V; Flashman, E; Chowdhury, R; Mohr, C; Liénard, B; Zondlo, J; Oldham, N; Clifton, I; Lewis, J; McNeill, L; Kurzeja, R; et al. (2006)
Cellular and physiological responses to changes in dioxygen levels in metazoans are mediated via the posttranslational oxidation of hypoxia-inducible transcription factor (HIF). Hydroxylation of conserved prolyl residues in the HIF-alpha subunit, catalyzed by HIF prolyl-hydroxylases (PHDs), signals for its proteasomal degradation. The requirement of the PHDs for dioxygen links changes in dioxygen levels with the transcriptional regulation of the gene array that enables the cellular response to chronic hypoxia; the PHDs thus act as an oxygen-sensing component of the HIF system, and their inhibition mimics the hypoxic response. We describe crystal structures of the catalytic domain of human PHD2, an important prolyl-4-hydroxylase in the human hypoxic response in normal cells, in complex with Fe(II) and an inhibitor to 1.7 A resolution. PHD2 crystallizes as a homotrimer and contains a double-stranded beta-helix core fold common to the Fe(II) and 2-oxoglutarate-dependant dioxygenase family, the residues of which are well conserved in the three human PHD enzymes (PHD 1-3). The structure provides insights into the hypoxic response, helps to rationalize a clinically observed mutation leading to familial erythrocytosis, and will aid in the design of PHD selective inhibitors for the treatment of anemia and ischemic disease.